Shifts in sex-specific immune gene expression in a beetle with parental care - Nikoletta A. Nagy; José O. Valdebenito; Johanna Lévai-Kiss; Zoltán Rádai; András Kosztolányi; Tamás Székely; Zoltán Barta (Scientific Reports)
Abstract Males and females generally differ in resource investment strategies in order to maximise reproductive output. These strategies involve the control of important systemic processes such as self-maintenance and immune activity, which in turn could be traded-off against aspects of reproduction in a sex-specific manner. While some aspects of this immunomodulation have been previously shown in domestic animals, sex-specific immune modulation using repeated sampling over the breeding period has rarely been tested in the wild. Here we used Lethrus apterus, a sexually dimorphic beetle with parental care, to investigate the association between sex roles (e.g. offspring provisioning) and sex-specific immune gene expression. By determining the immune gene activation of males and females at five successive moments within the active season, we found that their sex-specific immune gene expression varies substantially across the active season, alternating between male bias to female bias and vice versa. Though, when pooling all sampling dates together, there was no overall difference in the number of up-regulated immune genes between the sexes. Sex roles in this beetle are associated with energetically demanding behaviours that could potentially explain our results. We highlight the importance of successive sampling protocols to understand ecological dynamics in the wild.